Overview of Curricula About Pain in Physical Therapist Education Programs in Brazil: A Faculty Survey. Issue 11 (6th August 2018) - Venturine, Jéssica S; Pires, Gabriel M T; Pereira, Monique L; Monteiro, Michelle G M; Meziat-Filho, Ney; Nogueira, Leandro C; Reis, Felipe J J
Abstract: Background: Educating health professionals about pain (pain education) during undergraduate studies may be an important step in changing ineffective pain management practices. Objective: The objective of this study was to assess the extent of pain education in current accredited physical therapist education programs in Brazil. Design: This study was designed as a cross-sectional survey study. Methods: Brazilian physical therapist education programs accredited by the Ministry of Education participated in this study. The main outcome measures were frequency of a specific curriculum about pain (pain curriculum) in physical therapist education programs and content analysis according to discipline-specific pain curriculum recommendations developed by the International Association for the Study of Pain. Results: A total of 811 physical therapist education programs in Brazil were identified. After duplicates and universities no longer offering a physical therapist education program were removed, a total of 566 physical therapist education programs were left; 399 of the 566 (70.5%) provided information about the curriculum on their websites. Among the identified physical therapist education programs with available curricula, 26 (6.5%) had a specific course about pain (pain course), covering a mean of 44.3 hours. Limitations: Limitations included the inability to cover all the physical therapist education programs in Brazil and the inability to identify whether pain content is distributed in other disciplines such as pediatrics, geriatrics, and neurological and orthopedic physical therapy. Conclusions: Most Brazilian physical therapist education programs do not offer a specific pain course. When a pain course is presented in the curriculum, some content recommended for physical therapist education programs by the International Association for the Study of Pain is not covered. The absence of a pain course in physical therapist education programs may have implications for pain management. To the best of our knowledge, this is the first study about pain education in physical therapist education programs in Brazil.